Metformin Protects the Heart Against Hypertrophic and Apoptotic Remodeling After Myocardial Infarction - Loi, Halyna; Boal, Frederic; Tronchere, Helene; Cinato, Mathieu; Kramar, Solomiia; Oleshchuk, Oleksandra; Korda, Mykhaylo; Kunduzova, Oksana (Frontiers in Pharmacology, 2019)
Cardiovascular complications are the most prevalent cause of morbidity and mortality in diabetic patients. Metformin is currently the first-line blood glucose-lowering agent with potential relevance to cardiovascular diseases. However, the underpinning mechanisms of action remain elusive. Here, we report that metformin represses cardiac apoptosis at least in part through inhibition of the FoxO1 pathway. In a mouse model of ischemia-reperfusion (I/R), treatment with metformin attenuated I/R-induced cardiac and hypertrophic remodeling after 14 days of post-reperfusion. Additionally, cardiac expression of brain-like natriuretic peptide (BNP) was significantly reduced in metformin-treated mice after 14 days of cardiac I/R. In cultured H9C2 cells, metformin counteracted hypertrophic and apoptotic responses to metabolic or hypoxic stress. FoxO1 silencing by siRNA abolished anti-apoptotic effect of metformin under hypoxic stress in H9C2 cells. Taken together, these results suggest that metformin protects the heart against hypertrophic and apoptotic remodeling after myocardial infarction.